Pemanfaatan Blogger Web Desain Sebagai Media Digital Sarana Promosi UMKM Florist Dan Gift Tangankita.Id - Alvina Desti Ananta; Rindi Febrianti (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This Project-Based Learning (PBL) activity was conducted at Tangankitaa.id. This research examines the digital promotional strategies employed by the MSME (Micro, Small, and Medium Enterprise) tangankita.id, a florist and gift business specializing in flower arrangements, hampers, and personalized gifts. Through the use of social media platforms like Instagram, marketplaces, and websites, this business is able to reach a wider consumer base. The research focused on analyzing promotional content, visual design quality, and the effectiveness of customer interactions. The results indicate that visual-based promotions (product photos/videos) and personalized gift offerings are key factors in increasing consumer appeal.